Whither opportunity? : rising inequality, schools, and children's life chances - Duncan, Greg J.; Murnane, Richard J. (Russell Sage Foundation ; Spencer Foundation, 2011)
In Whither Opportunity?, a team of economists, sociologists, and experts in social and education policy examines the corrosive effects of unequal family resources, disadvantaged neighborhoods, insecure labor markets, and worsening school conditions on K-12 education. This groundbreaking book illuminates the ways rising inequality is undermining the ability of schools to provide children with an equal chance at academic and economic success. Whither Opportunity? shows that from earliest childhood, parental investments in children s learning affect reading, math, and other attainments later in life. Contributor Meredith Phillip finds that between birth and age six, wealthier children spend significantly more time than poor children on child enrichment activities such as music lessons, travel, and summer camp. Greg Duncan, George Farkas, and Katherine Magnuson demonstrate that a child from a poor family is two to four times as likely as a child from an affluent family to have classmates with low skills and behavior problems. As a result of such disparities, contributor Sean Reardon finds that the gap between rich and poor children s achievement scores is now much larger than it was 50 years ago. Such income-based gaps persist across the school years, as Martha Bailey and Sue Dynarski document in their chapter on the growing income-based gap in college completion. Whither Opportunity? also reveals the profound impact of environmental factors on children s educational progress. Elizabeth Ananat, Anna Gassman-Pines, and Christina Gibson-Davis show that local job losses such as those caused by plant closings can lower the test scores of students with low socioeconomic status, even students whose parents have not lost their jobs. And David Kirk and Robert Sampson show that teacher commitment, parental involvement, and student achievement in schools in high-crime neighborhoods all tend to be low.